Pemberdayaan Masyarakat melalui Program Bank Sampah untuk Pengelolaan Lingkungan Berkelanjutan - Komang Widhya Sedana Putra P; Rian Arif Fahendra; Sahri Aflah Ramadiansyah; I Putu Dharmawan Pradhana (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The management of waste is an issue that must be taken into consideration in any climate change mitigation debate. The Waste Bank initiative in Padang Indah Hamlet Hall, Padangsambian Klod area has been successful in reducing waste volume through sorting recycling. This bottom-up approach has not only helped in cleaning the environment but also enhanced economic activities in the area. Objective: The aim of this study is to assess the effectiveness of the Waste Bank in fostering public environmental cleanliness, increasing awareness, and enhancing economic activities. Further, it seeks to understanding how waste sorting and recycling leads to environmental improvement and greater community participation. Method: Data was collected for this study using field observations, focus group interviews with selected Waste Bank participants, and comparison of waste reduction statistics. The study was interested in the processes of waste collection, sorting, and selling to understand its impact on economic and community participation. Result: The overall results of the study point that the Waste Bank contributes in improving the environmental welfare, encourages the people to learn how to take care of waste, and enhances the participants’ income. The program encourages more people and organizations to value and take action in protecting the environment through sustainable community efforts. Conclusion: The Waste Bank provides an all-embracing solution for waste management by integrating economic and socio-cultural aspects. It leads to a cleaner environment and participates community sustainable waste management by encouraging local involvement.